What are the chances? : why we believe in luck - Blatchley, Barbara (Columbia University Press, 2021)
"Most of us, no matter how rational we think we are, have a lucky charm, a good-luck ritual, or some other custom we follow in the hope that it will lead to a good result. Is the idea of luckiness just a way in which we try to impose order on chaos? Do we live in a world of flukes and coincidences, good and bad breaks, with outcomes as random as a roll of the dice-or can our beliefs help change our luck? What Are the Chances? reveals how psychology and neuroscience explain the significance of the idea of luck. Barbara Blatchley explores how people react to random events in a range of circumstances, examining the evidence that the belief in luck helps us cope with a lack of control. She tells the stories of lucky and unlucky people-winning the lottery multiple times, surviving seven brushes with death, finding an apparently cursed Neanderthal mummy-as well as the accidental discoveries that fundamentally changed what we know about the brain. Blatchley considers our frequent misunderstanding of randomness, the history of luckiness in different cultures and religions, the surprising benefits of magical thinking, and many other topics. Offering a new view of how the brain handles the unexpected, What Are the Chances? shows why an arguably irrational belief can-fingers crossed-help us as we struggle with an unpredictable world"--